Experimental investigation of solid particles flow in a conical spouted bed using radioactive particle tracking. Issue 1 (3rd September 2015) - Spreutels, Laurent; Haut, Benoit; Legros, Robert; Bertrand, Francois; Chaouki, Jamal
Abstract : Solid particles flow in a conical spouted bed is characterized by radioactive particle tracking. The influence of operating conditions on key parameters of this flow is evaluated and discussed: the morphology of the solid bed is not strongly influenced by the forces exerted by the gas on the solid particles, but rather by geometrical considerations; the particles spend approximately 8% of their time in the spout in all experiments; it is the force exerted on the solid particles by the gas that directly controls the volumetric flow rate between adjacent regions, and not the amount of particles in the bed; as U/Ums increases, the volume of solid particles in the annulus decreases, the volume of solid particles in the fountain increases and the volume of solid particles in the spout remains constant. Correlations to predict key flow parameters as functions of operating conditions are also established and discussed. © 2015 American Institute of Chemical Engineers AIChE J, 62: 26–37, 2016